IMPLEMENTASI PROGRAM E-WARONG MANDIRI JAYA KOTA SEMARANG - Muhammad Arif Febrian; Hesti Lestari; Dewi Rostyaningsih (Journal of Public Policy and Management Review, 2023)
The E-Warong Mandiri Jaya program is a poverty alleviation program in Indonesia through the distribution of food assistance which is carried out electronically and managed by the community independently by utilizing capital from the government. The implementation of the E-Warong program determines the success of increasing community welfare. The problem in this study is shown by the decrease in the number of EWarong customers from year to year and the change in the distribution system to cash which is not in accordance with the concept of the E-Warong program which carries the electronic theme. This study aims to analyze the implementation of the E-Warong Mandiri Jaya program along with its driving and inhibiting factors. Method study that is chosen is descriptive qualitative by collecting data through interviews, observation, and documentation. This research is studied using implementation theory from Charles O. Jones which is reviewed from 3 aspects, namely organizational aspects, interpretation aspects, and application aspects. Based on the results of the research, the implementation of E-Warong Mandiri Jaya has not been successful because there are several inhibiting factors caused by the existence of people who are dissatisfied with the assistance provided so they shop at other stalls, besides that there is a policy issued by the Indonesian Ministry of Social Affairs which causes overlapping directions so that the implementation of EWarong Mandiri Jaya is not optimal